Keuntungan Maksimum dengan Program Linear pada UMKM Noga Sari - Palahudin Palahudin; Firmansyah Firmansyah; Dani M Ramdani; Rodiko Gorat; Anto Wijaya (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Home industries such as Noga Sari, daily produce processed nuts with original and chocolate flavors. With previous research that obtained information about the composition of many units of each variant in production, as well as determining the maximum profit obtained optimally, to determine this, as a consequence of the analysis, the maximum profit of UMKM Noga Sari must be calculated. To this end, a linear program is used to calculate the maximum profit using the simplex approach through a solver. The quantitative method is applied in this research. Information gathered from talks with the UMKM Noga Sari's owner.